Idiomatic Expressions of Number in Persian and English - Parvaresh, Vahid; Ghafel, Banafsheh (Richtmann Publishing, 2012)
Numbers are widely used to form such metaphorical idioms as ‘at sixes and sevens’, ‘to be on cloud nine’ and ‘three sheets tothe wind’. A question arises as to how these number-related expressions acquire their metaphorical significance. Following Lakoff andJohnson (1980) and in the light of Conceptual Metaphor Theory, the present study investigates the relationship between language andculture in the construction of idiomatic expressions of number in English and Persian. The working hypothesis in the present study is thatalthough numbers have similar denotations across cultures, idiomatic expressions of number may represent culture-specific concepts.